Efektivitas Layanan Arsip dalam Pembuatan Salinan Perizinan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Kubu Raya - Sandi Yudha, Eka Nesti Ardian (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze the performance of the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Kubu Raya Regency in efforts to increase regional investment. The research method used is descriptive qualitative analysis with a case study approach. Data were obtained through in-depth interviews, observations, and documentation studies. The results show that DPMPTSP Kubu Raya Regency has implemented various service innovations that have successfully increased the efficiency of the licensing process and investment realization. The implementation of the Online Single Submission (OSS) system and the "Jemput Bola" service has reduced licensing process time by up to 30%. Focus on developing superior sectors, especially agribusiness, has contributed 40% of total investment. The "UMKM Go Digital" program has successfully increased MSME turnover by 30%. However, challenges remain, such as digital infrastructure gaps and inter-agency coordination. This study concludes that DPMPTSP's comprehensive approach in regulatory reform, infrastructure development, and institutional capacity building has contributed significantly to creating a conducive investment climate in Kubu Raya Regency.